No bullying in our community home/school partnership strategies - Sleeth, Shannon; Collins, Cath; Garner, Simon; Leigh, Richard; Video Education Australasia (Australia : Video Education Australasia, 2005)
This program will support parents who want to work in partnership with their child's school to bring about a suitable outcome for children involved in bullying
Title from title screen
Executive producer, Mark McAuliffe ; editor, Shannon Sleeth ; sound, Wayne Martin, Alexy Gudimenko
Voice over: Mark Collard
DVD Format
Keywords: Bullying in schools; Bullying